A State of Disturbance. - Heardman, Adam (Art Monthly, 2023)
An interview with artist Luke Fowler is presented. Fowler talks about the portrait film "Being in a Place" about filmmaker Margaret Tait, the Scottish landscape imagery associated with the Ossian epic style cycle of poems and its ersatz highland myths, and differences and separation of film, video art and cinema. She discusses the importance of bringing subjectivity in experimental filmmaking, the principles of image-making, and influence of subjectivity and psychic experience on filmmaking.